2015
DOI: 10.3892/ol.2015.3103
|View full text |Cite
|
Sign up to set email alerts
|

Primary mediastinal giant liposarcoma with smooth muscle and neural differentiation: A case report

Abstract: Abstract. Liposarcoma has previously been described in Western studies, however, such cases are rarely reported in the mediastinum. In addition, the presence of a liposarcoma with smooth muscle and neural differentiation has not been previously reported. Thus, the present study describes the rare case of a 28-year-old Chinese male admitted to our hospital with the symptoms of chest tightness and shortness of breath due to a recurrent fibrolipoma in the mediastinum. The resected tumor measured 23 cm at its larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In the literature, most studies of GMTs are published as case reports. [ 11 - 15 ] Our study is, therefore, valuable as it analyzed a series of clinical cases for guiding the treatment of GMTs. Our study results showed a good prognosis in both our cohort and the cases retrieved from the NCBI database using RS.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, most studies of GMTs are published as case reports. [ 11 - 15 ] Our study is, therefore, valuable as it analyzed a series of clinical cases for guiding the treatment of GMTs. Our study results showed a good prognosis in both our cohort and the cases retrieved from the NCBI database using RS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 9 ] These tumors are characterized by amplification of MDM2 and CDK4 genes on chromosome 12. [ 10 ] Most of these mass are identified incidentally or worked up secondary to complications by compression or irritation of adjacent structures. The possible symptoms of mediastinal liposarcoma are dyspnea, wheezing, chest pain, cough, SVC (superior vena cava) compression and voice hoarseness.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the MDM2 and CDK2 genes that are located on chromosome 12 is a distinguishing feature of the tumour [ 4 ]. In addition to advanced age, contact with radiation and toxic substances is also considered to be a major risk factor for the condition [ 5 ].…”
Section: Introductionmentioning
confidence: 99%